Novel Histone Deacetylase (HDAC) Inhibitor Induces Apoptosis and Suppresses Invasion via E-Cadherin Upregulation in Pancreatic Ductal Adenocarcinoma (PDAC) - Katja Schiedlauske; Alina Deipenbrock; Marc Pflieger; Alexandra Hamacher; Jan Hänsel; Matthias U. Kassack; Thomas Kurz; Nicole E. Teusch (MDPI AG, 2024)
Pancreatic ductal adenocarcinoma (PDAC) is the most lethal form of pancreatic cancer characterized by therapy resistance and early metastasis, resulting in a low survival rate. Histone deacetylase (HDAC) inhibitors showed potential for the treatment of hematological malignancies. In PDAC, the overexpression of HDAC 2 is associated with the epithelial-mesenchymal transition (EMT), principally accompanied by the downregulation of the epithelial marker E-cadherin and increased metastatic capacity. The effector cytokine transforming growth factor-β (TGF β) is known to be a major inducer of the EMT in PDAC, leading to high metastatic and invasive potential. In addition, the overexpression of HDAC 6 in PDAC is associated with reduced apoptosis. Here, we have demonstrated that a novel HDAC 2/6 inhibitor not only significantly increased E-cadherin expression in PANC-1 cells (5.5-fold) and in 3D PDAC co-culture spheroids (2.5-fold) but was also able to reverse the TGF-β-induced downregulation of E-cadherin expression. Moreover, our study indicates that the HDAC inhibitor mediated re-differentiation resulting in a significant inhibition of tumor cell invasion by approximately 60% compared to control. In particular, we have shown that the HDAC inhibitor induces both apoptosis (2-fold) and cell cycle arrest. In conclusion, the HDAC 2/6 inhibitor acts by suppressing invasion via upregulating E-cadherin mediated by HDAC 2 blockade and by inducing cell cycle arrest leading to apoptosis via HDAC 6 inhibition. These results suggest that the HDAC 2/6 inhibitor might represent a novel therapeutic strategy for the treatment of PDAC tumorigenesis and metastasis.